Compound Heterozygosity for Two Novel Missense Mutations in the Prothrombin Gene in a Patient with a Severe Bleeding Tendency - Poort, S R; Landolfi, R; Bertina, R M (Thrombosis and Haemostasis, 1997)
The abnormal prothrombin gene of an Italian patient with a severe bleeding tendency and hypoprothrombinemia was selected for study and compared with the prothrombin genes of healthy controls. All the coding and their flanking regions and the 5ʹ- and 3ʹ-UT regions of the prothrombin gene were screened by analyzing the nucleotide sequence of the corresponding PCR products. The patient was found to be heterozygous for two novel point mutations: one at nucleotide 4251 in exon 6, which changes the codon for cysteine-138 (TGC) in the kringle 1 domain to that for tyrosine (TAC), and one at nucleotide 8812 in exon 10, which results in the replacement of tryptophan-357 (TGG) by cysteine (TGT) in the catalytic domain. Her mother was heterozygous for the Cys-138 Tyr mutation and her father heterozygous for the Trp-357 Cys mutation. Several other sequence variations were identified in the prothrombin genes from control individuals. Only the variations at nucleotide 4203 and 10253 could be established as polymorphisms.